Computational Analysis Supports an Early, Type 17 Cell-Associated Divergence of Blunt Trauma Survival and Mortality*. Issue 11 (November 2016) - Abboud, Andrew; Namas, Rami A.; Ramadan, Mostafa; Mi, Qi; Almahmoud, Khalid; Abdul-Malak, Othman; Azhar, Nabil; Zaaqoq, Akram; Namas, Rajaie; Barclay, Derek A.; Yin, Jinling; Sperry, Jason; et al.
Abstract : Objective: Blunt trauma patients may present with similar demographics and injury severity yet differ with regard to survival. We hypothesized that this divergence was due to different trajectories of systemic inflammation and utilized computational analyses to define these differences. Design: Retrospective clinical study and experimental study in mice. Setting: Level 1 trauma center and experimental laboratory. Patients: From a cohort of 493 victims of blunt trauma, we conducted a pairwise, retrospective, case-control study of patients who survived over 24 hours but ultimately died (nonsurvivors; n = 19) and patients who, after ICU admission, went on to be discharged(survivors; n = 19). Interventions: None in patients. Neutralizing anti-interleukin-17A antibody in mice. Measurements and Main Results: Data on systemic inflammatory mediators assessed within the first 24 hours and over 7 days were analyzed with computational modeling to infer dynamic networks of inflammation. Network density among inflammatory mediators in nonsurvivors increased in parallel with organ dysfunction scores over 7 days, suggesting the presence of early, self-sustaining, pathologic inflammation involving high-mobility group protein B1, interleukin-23, and the Th17 pathway. Survivors demonstrated a pattern commensurate with a self-resolving, predominantly lymphoid response, including higher levels of the reparative cytokine interleukin-22. Mice subjected to trauma/hemorrhage exhibited reduced organ damage when treated with anti-interleukin-17A. Conclusions: Variable type 17 immune responses are hallmarks of organ damage, survival, and mortality after blunt trauma and suggest a lymphoid cell–based switch from self-resolving to self-sustaining inflammation. Abstract : Supplemental Digital Content is available in the text.